Organization of the implementation of an investment project for the production of sanitary products in the Republic of Kazakhstan - Akhmetov, Нуралы; Tarikhov, Асылан; Hafiz, Қайрат (Рroblems of engineering and professional education, 2023)
Construction is a complex production, which involved numerous industrial structures and use their products. Domestic construction production is an area where used building materials, products and designs, including from foreign countries. It is known that the maximum use of local construction materials, products and structures improves the efficiency of building production and reduces the cost of construction of buildings and structures